ANALISIS KINERJA BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN DESA DI DESA PULAU PANDAN KECAMATAN LIMUN KABUPATEN SAROLANGUN - Yuliana, Deresty (Universitas Jambi, 2024)
This study on the analysis of the performance of village-ownedenterprises (BUMDES) Pandan Island aims to determine how todetermine how the effectiveness of the performance of BUMDESto increase the income of the village “Pandan Island”. This studyuses qualitative descriptive method. Informants were taken bymeans of purposeful samples and research data obtainedthrough research data obtained through secondary data,observation, and in-depth interviews. The results showed thatBUMDES